UTILIZING MUSIC AS A TOOL FOR SECOND LANGUAGE ACQUISITION - Icha Trizzeta Indriana; Nurhasanah, Nurhasanah (ReALL - Research on Applied Linguistics and Literature, 2024)
Psycholinguistics or psychology of language is the study of the relationship between linguistic factors and psychological aspects. The main subject of psycholinguistic research is the study of the cognitive processes underlying language comprehension and production, and the way the cultural environment interacts with both. This research reports the result of case study that investigate the impact of utilizing music as a tool for second language acquisition (SLA) for English literature students at University of Sebelas April Sumedang. The study aims to investigate how exposure to song lyrics helps learners recall vocabulary and improve pronunciation, contributing to their overall language development. The main findings are music has an impact for participant skills language, especially for reading skills. This research used qualitative method. The data is collected through observation and then describe it descriptively. The results showed that from four participants could recall and remember some words from the song lyrics and pronounce them when speaking. The total of nine parts of speech there are pronoun, noun, verb, adjective, adverb, preposition, conjunction, determiner, and interjection, that appear is 624 times which is divided into; 183 times for pronoun, 110 times for noun, 136 times for verb, 32 times for adjective, 6 times for adverb, 23 times for preposition, 39 times for conjunction, 87 times for determiner, and 8 times for interjection. Through this research, it is expected to help further research on psycholinguistics about the use of music as a second language acquisition tool. By integrating songs into the English learning process, educators can create a more engaging environment that motivates students to develop their language skills. The use of music as a second language acquisition tool is expected to continue to be developed in the English learning process that is interesting for students.